A novel system for optically localized soliton pulse in a nano-waveguide - Pornsuwancharoen, N.; Amnuaykarn, K.; Yupapin, P. P. (My University, 2010)
We propose a novel optical system that can be used to trap (store) light coherently. The system consists of two micro and a nano-ring resonators that can be integrated into a single system, which can be employed to generate the large bandwidth by a soliton pulse within a Kerr type nonlinear medium. The balance between dispersion and nonlinear lengths of the soliton pulse exhibits the soliton behavior known as self-phase modulation, which introduces the optical output (i.e. gain) constant, which means that light pulse can be trapped, i.e. localized coherently within the nanowaveguide. The time independent soliton pulse is adiabatically localized within the nano-ring device. Results obtained have shown that the trapping of the localized temporal and spatial soliton pulses is achieved. © 2009 elseviegmbh. all rights reserved.
Keywords: Localized soliton; Optical memory; Quantum memory; Stop light; Store light